TOURISM EFFECTS ON EQUITY ANS SECURITY: PERSPECTIVES FROM LOCAL POOR PEOPLE - BENXIANG ZENG (ASEAN Journal on Hospitality and Tourism, 2005)
This paper analyses the effects of tourism on equity and the security of local poor households in China. Tourism is found to be an important income source for local households, although the poor get much less benefit than other households. While most stakeholders realized the inequity and disadvantages for the poor, there are significant differences in perceptions of tourism effects between local households and other stakeholders, as well as between the poor and other income groups. Stakeholders other than local households generally over-estimate positive tourism effects on local economic growth and underestimate the extent of cultural change. Households generally believe tourism increases their cash income, creates employment opportunities, and improves living standards. However, the poor are more circumspect than higher income groups about these effects. The poor consider that tourism development does not improve access to education opportunities, and are concerned about the widening gap between the poor and 'rich'. However, wealthy people were concerned about the negative social impacts of tourism, while the poor were more positive about tourism's effect on social security. The major barriers for the involvement of the poor in tourism are socio-economic, especially the lack education. The high cost of education and its effect on household expenditure, means that the poor are trapped and can rarely take advantage of the benefits of tourism. The study suggests a modification of the Sustainable Tourism-Eliminating Poverty model to include policies for reinvestment of tourism's economic benefits into human capital (education) to reduce the imbalance between household income and expenditure.